Enterprise Architecture Integrated Management Information System Untuk Optimalisasi Layanan Manajemen Pendidikan Tinggi - Yasinta Dewi Umi Latifah; Febriliyan Samopa (LPPM STIKOM Tunas Bangsa, 2024)
This study focuses on implementing Enterprise Architecture (EA) to address the challenges of integrating the higher education management systems at University X. Currently, the university faces issues of non-integration among its 4 service areas, each utilizing different platforms and manual business processes. As a solution, this research designs an integrated EA using the TOGAF ADM framework. The research process involves interviews with education stakeholders and gap measurements between the current and planned systems through questionnaires and focus group discussions. The results indicate that the EA design aligns with a validation score of 4.3, with a note on the need for attention to the details of data and technology architecture, as well as further analysis regarding cost priorities and human resources in the implementation roadmap. This study provides an EA blueprint to create an integrated information system, optimize business processes, and enhance services through the integration of data, applications, and technological development. The implementation of EA is expected to improve efficiency in 29 business activities currently carried out manually at University X